2015
DOI: 10.3390/ijms161226102
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin Attenuates Depressant-Like Behavior in Mice Subjected to Repeated Restraint Stress

Abstract: Increasing evidence has shown that oxidative stress may be implicated in chronic stress-induced depression. Several flavonoids with anti-oxidative effects have been proved to be anti-depressive. Myricetin is a well-defined flavonoid with the anti-oxidative, anti-inflammatory, anti-apoptotic, and neuroprotective properties. The aim of the present study is to investigate the possible effects of chronic administration of myricetin on depressant-like behaviors in mice subjected to repeated restraint (4 h/day) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 36 publications
3
34
0
Order By: Relevance
“…This is supported by previous findings, chronic restraint and CUS showed anxiety-like behavior, and this was reduced in the MYR-administrated group [1,31,32]. Riaz et al (2015) reported that CUS-exposed animals showed impaired spatial memory in the eight-arm radial maze [33], this is consistent with the present findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is supported by previous findings, chronic restraint and CUS showed anxiety-like behavior, and this was reduced in the MYR-administrated group [1,31,32]. Riaz et al (2015) reported that CUS-exposed animals showed impaired spatial memory in the eight-arm radial maze [33], this is consistent with the present findings.…”
Section: Discussionsupporting
confidence: 93%
“…The similar results were observed in the earlier studies, unpredictable subchronic stress affects memory through increased glucocorticoid levels which might have implications for brain plasticity and behavioral changes following the stress in rat's hippocampus [39]. Recognition memory was improved in MYR-ME treated, the possible mechanism could be decreasing corticosterone levels and increasing brain-derived neurotropic factor (BDNF) levels, previous study also reported that chronic restraint stress increased corticosterone levels and decreased BDNF levels, and this was normalized in the MYR treatment animals by attributing to MYRmediated antioxidative stress in the hippocampus [32].…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that loud unexpected sounds can raise levels of stress-related hormones (Burow et al, 2005). Both restraint and social stress are common in laboratory animals (Stone and Quartermain, 1997; Ma et al, 2015). Simple handling of an animal, putting it in a new environment, and cage changes can also raise levels of stress in animals (Seggie and Brown, 1975; Duke et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in mice subjected to restraint stress to induce cognitive deficits and depression, myricetin improved spatial memory and depression-like behavior. Myricetin also normalized the decreased brain-derived neurotrophic factor (BDNF) levels observed in the hippocampus [13,14]. Myricetin was also found to protect 1-methyl-4-phenylpyridinium (MPP+)-treated MES23.5 dopaminergic cells-which exhibit similar properties to primary neurons originating in the substantia nigra, a lesion of PD-by inhibiting MAPK kinase and c-Jun N-terminal kinase (JNK) activation and having an anti-oxidative role [15].…”
Section: Introductionmentioning
confidence: 98%